The estimation algorithm of operative capabilities of complex countermeasures to resist UAVs. (June 2019) - Korobiichuk, Igor; Danik, Yuriy; Samchyshyn, Oleksyj; Dupelich, Sergiy; Kachniarz, Maciej
The proposed observation model provides for calculating the probability of detection of different types of unmanned aerial vehicle (UAV) at a certain range with regard to their tactical and technical characteristics and security equipment capabilities. The comparison of the obtained values of generalized indicators of security equipment use efficiency is based on a specified criterion. To take into account factors that significantly affect a modeling object, calculations are carried out under specified conditions and restrictions. UAVs should be detected until a covering object gets in a swath width given the time required for countermeasures. Based on the software implementation of the algorithm we have evaluated the efficiency of use of hypothetical security equipment for detecting certain types of UAVs, and defined means of further use or improvement.